Identification of Patients with a High Risk of Developing Precancerous Colon Diseases at the Outpatient Stage - Anastasiia F. Gayazova; Tatyana V. Bolotnova (Кубанский научный медицинский вестник)
Aim. To identify patients with a high risk of precancerous diseases of the colorectal region for colonoscopy assignment in the practice of a district physician.Materials and methods. 122 patients were surveyed who underwent colonoscopy by the appointment of a district physician at the Municipal Polyclinic No. 3 in Tyumen. All examined patients were divided into two groups according to colonoscopy: with colon polyps — 64 (52.5 %) and without colon polyps — 58 patients (47.5 %).Results. The mean age of patients in the group with colon polyps was 59.8 ± 4.7 years, in the second group — 58.2 ± 4.8 years. In the group with colon polyps, more patients exhibited a low physical activity and poor nutrition compared to the group without colon polyps. Erosive gastritis and obesity prevailed in patients of the group with colon polyps as compared to the second group. The number of patients who smoked and drank alcohol prevailed in the group with colon polyps, in comparison with the second group. Patients with colon polyps were twice as likely to have a burdened hereditary history of colorectal cancer as those without colon polyps. Conclusion. Thus, the group of high risk of colon polyps included patients with risk factors: smoking, low physical activity and burdened hereditary history of colon cancer, as well as erosive gastritis in the history.